UJI AKTIVITAS ANTIPLASMODIUM EKSTRAK BENALU SECARA IN VIVO PADA MENCIT GALUR SWISS - Faiqoh, Zulfa; Baskara, Anak Agung Ngurah Nata; Budi, Danang Setia; Putra, Pramana Pananja; Nitari, Wahyu; Solikhah, Eti Nurwening (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
Malaria is one of the most prevalent tropical disease in the world. Until now, the use of antimalarials in malaria patients generated a lot of resistance so many scientists began the development of research using herbal plant ingredients, for example mistletoe (Dendrophthoe pentandra) This study was conducted to determine the effect of antiplasmodium in vivo. Antiplasmodium test conducted on P. berghei which were injected into mice suppression method. The results show that the Dendrophthoe pentandra extract has antiplasmodium activity with ED50 of 146,2 mg/kgBW. It can be concluded that Dendrophthoe pentandra has the potential as an antimalarial agent in vivo. Keywords: Dendrophthoe pentandra, malaria, antiplasmodium, mice, parasitemia,Â Plasmodium berghei.